Local-global interaction buckling and load carrying capacity calculation method of cold-formed steel built-up closed section column - Wang, Shuaibing; Zhou, Tianhua; Liao, Tianwei; Wang, Yan; Sang, Liurui; Zhang, Lei (Structures (Oxford), 2025)
Cold-formed steel built-up closed section columns, composed of the lipped channel and channel section components connected by self-tapping screws, have been widely studied both experimentally and theoretically. However, a universally accepted design method for these columns has yet to be established. This research aims to develop a load carrying capacity curve that considers local-global interaction buckling for these columns through both experimental and numerical analyses. Axial compression tests were conducted on 18 built-up closed-section columns to assess how cross-sectional dimensions and slenderness ratios affect load carrying capacity. A validated finite element model was developed for this purpose, and a parametric analysis was performed to examine the impact of slenderness ratio, web height-thickness ratio, and screw spacing. The resulting data were used to generate local-global interaction buckling load-carrying capacity curves. By combining experimental and numerical analyses, this study proposes an original method for calculating the local-global interaction buckling load carrying capacity of cold-formed steel built-up closed section columns. Finally, predictions from the proposed method were compared with those from the effective width method (EWM) and the direct strength method (DSM). Results indicate that the EWM provides conservative estimates, while the DSM is less accurate. The proposed method achieves an error of less than 10 %, demonstrating high accuracy and a simpler calculation process.